The determinants of non-traditional agricultural exports' growth in Ghana - Sylvester N. Ayambila; Umar Adam; Benjamin Tetteh Anang (Cogent Economics & Finance, 2023)
The Nontraditional Agricultural Exports (NTAE) sub-sector is a key contributor to agricultural gross domestic product (GDP) in several developing countries. It has the potential to create jobs and contribute to enhancing food and nutrition security, hence an important pillar to the economies of several countries including Ghana. This study, therefore, examines the factors driving the growth of nontraditional agricultural exports in Ghana using an Autoregressive Distributive Lag (ARDL) model. The study was based on secondary data from the World Development Indicators (WDI) and Food and Agriculture Organization (FAO). The study identified real GDP to be a significant determinant of NTAE's growth in both contemporaneous and lag forms. Other variables including inflation, gross capital formation and foreign direct investment influence NTAE's growth through their lag values. Exchange rate, inflation and RGDP significantly determine the growth of NTAEs in the long-run. The study further identified a co-integrating relationship between NTAE and other explanatory variables. The Error Correction Model showed an adjustment speed of 0.41, indicating that 41% adjustment will occur within the first year and it will take 2.4 years for the system to return to equilibrium in the long-run. Based on the findings, the study recommends that Ghana Export Promotion Authority (GEPA) adopts promotional strategies including providing incentive packages to farmers, exhibitions and trade fairs to curtail the declining trend in the growth of the NTAE's sector. The Ministry of Food and Agriculture (MoFA) should educate farmers on the use of acceptable agronomical practices in the production field. Lastly, Ghana Investment Promotion Center (GIPC) and MoFA should collaborate to identify strategic areas for domestic support and foreign direct investment in the NTAE's sub-sector to ensure it grows and contributes towards socio-economic development in Ghana.
Keywords: 330; autoregressive distributive lag model; Ghana; growth; nontraditional agricultural exports